Ethnic Differences in Thrombotic Profiles of Acute Coronary Syndrome Patients and Relationship to Cardiovascular Outcomes: A Comparison of East Asian and White subjects - Suh, Jung-Won; Memtsas, Vassilios; Gue, Ying X; Cho, Hyoung-Won; Lee, Wonjae; Kang, Si-Hyuck; Gorog, Diana A. (Thrombosis and Haemostasis, 2023)
Background East Asians (EAs), compared to white Caucasians (W), have a lower risk of ischemic heart disease and a higher risk of bleeding with antithrombotic medications. The underlying mechanisms are incompletely understood.Objectives We sought to compare thrombotic profiles of EA and W patients with myocardial infarction (MI) and relate these to cardiovascular outcomes.Methods In a prospective study in the United Kingdom and Korea, blood samples from patients (n = 515) with ST- or non-ST-elevation MI (STEMI and NSTEMI) were assessed using the Global Thrombosis Test, measuring thrombotic occlusion (OT) and endogenous fibrinolysis (lysis time [LT]). Patients were followed for 1 year for major adverse cardiovascular events (MACE) and bleeding.Results EA patients showed reduced OT (longer OT) compared to W (646 seconds [470–818] vs. 436 seconds [320–580], p < 0.001), with similar LT. In STEMI, OT (588 seconds [440–759] vs. 361 seconds [274–462], p < 0.001) and LT (1,854 seconds [1,389–2,729] vs. 1,338 seconds [1,104–1,788], p < 0.001) were longer in EA than W. In NSTEMI, OT was longer (OT: 734 seconds [541–866] vs. 580 seconds [474–712], p < 0.001) and LT shorter (1519 seconds [1,058–2,508] vs. 1,898 seconds [1,614–2,806], p = 0.004) in EA than W patients. MACE was more frequent in W than EA (6.3 vs. 1.9%, p = 0.014) and bleeding infrequent. While OT was unrelated, LT was a strong independent predictor of MACE event after adjustment for risk factors (hazard ratio: 3.70, 95% confidence interval: 1.43–9.57, p = 0.007), predominantly in W patients, and more so in STEMI than NSTEMI patients.Conclusion EA patients exhibit different global thrombotic profiles to W, associated with a lower rate of cardiovascular events.
Keywords: myocardial infarction; ethnicity; thrombotic status; fibrinolysis; East Asian